Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

As the question states I am trying to find $\frac{d^2V}{dq^2}$ of $3V^2+2q=2Vq$. I managed the first derivative and got: $$\frac{dV}{dq}=\frac{V-1}{3V-q}$$ However, when I did the second derivative I got: $$\frac{d^2V}{dq^2}=\frac{(V-1)(3V-2q+3)}{(3V-q)^3}$$ Which may or may not be right. What I am wondering about is: the book gives the answer $$\frac{d^2V}{dq^2}=\frac{(2q-3V-3)}{(1-V)^2}$$ How can I simplify my answer to get what they got, or in the case that my answer is completely wrong, could someone explain how to get to their answer.

share|improve this question

3 Answers 3

up vote 2 down vote accepted

I think your book is wrong. I got the same first and second derivatives as you did.

Now solving for $V$ from the original equation, we get $$V_{1,2} = \frac{q \pm \sqrt{q^2 - 6q}}{3}.$$

Let's try $q = 8$. Then $V_1 = 4$ and $V_2 = 4/3$. Then according to the second derivative you, I, and bgins computed

$$V_1''(8) = \frac{(4-1)(3\cdot4+3-2\cdot8)}{(3\cdot4-8)^3} = \frac3{64}$$

$$V_2''(8) = \frac{(4/3-1)(3\cdot4/3+3-2\cdot8)}{(3\cdot4/3-8)^3} = \frac3{64}$$

According to your book's second derivative,

$$V_1''(8) = \frac{2\cdot8-3\cdot4-3}{(1-4)^2} = \frac19$$

$$V_2''(8) = \frac{2\cdot8-3\cdot4/3-3}{(1-4/3)^2} = 81 $$

This does not match, so there is no way to reconcile your book's answer with yours, no matter what additional constraint we add on $V$.

share|improve this answer

If you differentiate $$ 3VV'+1=V+qV', $$ (from which your $V'$ follows) you get $$ 3(V')^2+3VV''=2V'+qV'' $$ $$ \eqalign{ V'' &=\frac{V'(2-3V')}{3V-q}\\ &=\frac{(V-1)(2-3V')}{(3V-q)^2}\\ &=\frac{(V-1)(3V+3-2q)}{(3V-q)^3}.\\ } $$ You did it right. The question is whether $V-1=3V-q$ (or their cubes are equal, which is the same thing since $y=x^3$ is invertible). Now you can use the quadratic equation to represent $V$ in terms of $q$, but if you work it out, it's completely different. I think the book solution is either wrong, or, if you notice, their formula is really $$-\frac{V''}{(V')^3}.$$ Have they told you that $V'=-1$ by any chance?

share|improve this answer
    
Thanks for the answer! And, no, they did not say that $V'=-1$. –  E.O. Mar 19 '12 at 0:02

I get the same for $V''$ as you do. To simplify, use $2q(V-1) = 3V^2$, i.e.

$$\frac{(V-1)(3V-2q+3)}{(3V-q)^3} = \frac{3(V-1)(V+1) - 3V^2}{(3V-q)^3} = \frac{-3}{(3V-q)^3}$$ which I think looks nicer than the book's answer.

(See the other answer, something looks wrong or incomplete with the given answer.)

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.